(untitled) (Trabalho & Educação, 2017)
In these times of the so-called information society, we have been aware of social, cultural, political, economic and, of course, educational changes. Among the various changes in the educational eld, we have focused on the changes derived from the existence and development of the information and communication’s digital technologies that promoted reections on traditional educational paradigms, ways of teaching and learning, time and space, expansion of knowledge exchange spaces, educational policies, face-to-face and distance modalities; as well as in ways of relating and producing new knowledge that involves collaboration, sharing, participation, horizontality, learning communities, interaction, mediation, virtual learning environments, socialization, autonomy and networking. In this tangle of situations and provocations, we hypothesized that the convergence observed in other areas of knowledge – technology, communication and arts – and the increasingly constant use of distance learning, combined with face-to-face teaching, would be the basis of convergence in... ___ Em tempos da denominada sociedade da informação, estivemos atentos às modicações sociais, culturais, políticas, econômicas e, evidentemente, educacionais. Dentre as várias mudanças no campo educativo, focalizamos as alterações derivadas da presença e do desenvolvimento das tecnologias digitais da informação e da comunicação que promoveram reexões sobre os paradigmas educacionais tradicionais, os modos de ensinar e de aprender, o tempo e o espaço, a ampliação dos espaços de trocas de conhecimento, as políticas educacionais, as modalidades presenciais e a distância; assim como, nas formas de se relacionar e produzir novos conhecimentos que envolvem a colaboração, a partilha, a participação, a horizontalização, as comunidades de aprendizagem, a interação, a mediação, os ambientes virtuais de aprendizagem, a socialização, a autonomia e as redes. Nesse emaranhado de situações e de provocações, criamos como hipótese que a convergência vericada em outras áreas do conhecimento — tecnologia, comunicação e artes — e o uso cada vez mais constante da educação a distância (EaD), conjugada com o ensino presencial, consubstanciaria-se em convergência...